Insurance and Asymmetric Information in Wage Contracts: Evidence from an Online Experiment - Daniel Herbst (CESifo GmbH, 2025)
For workers facing uncertain output, fixed-wage contracts provide implicit insurance compared to self-employment or performance-based pay. But like any insurance product, these contracts are prone to market distortions through moral hazard and adverse selection. Using a model of wage contracts under asymmetric information, I show how these distortions can be identified as potential outcomes in a marginal treatment effects (MTE) framework. I apply this framework to a field experiment in which data-entry workers are offered a choice between a randomized fixed hourly wage and a piece rate. Using experimental wage offers as an instrument for hourly wage take-up, I find evidence of both moral hazard and adverse selection. Hourly wage contracts reduce worker productivity by an estimated 6.32 percent relative to the mean. Meanwhile, a 10 percent increase in the hourly wage offer attracts a marginal worker whose productivity is higher by 1.44 percent of mean worker output. Using semi-parametric MTE estimation, I calculate the welfare loss associated with asymmetric information and the marginal values of public funds (MVPFs) for a range of wage-based subsidy and tax policies. My estimates suggest that a 14-percent tax on performance-based pay can efficiently raise government revenue by mitigating adverse selection into fixed-wage contracts.
Keywords: J33; J38; M52; D82; 330; compensation structure; wage insurance; performance pay; adverse selection; moral hazard; information asymmetries; marginal treatment effects